ÜLKEMİZDEKİ HUZUREVLERİNİN DAĞILIMI VE BU DAĞILIMIN DÜŞÜNDÜRDÜKLERİ - VEHİD, Suphi (Cerrahpaşa Medical Journal, 2014)
Background.- The problems of the community are like skins of an onion. In spite of the population growth rate protection, population growth rate is the one of the main problems of Turkey and still seen higher than the developed countries. On the other hand increase of the diagnostic and treatment facilities cause a rise on the number of old age people. The percentage of the ageing people in our community is estimated to increase up to 9.3 % between the years 2015 - 2025. There is an imbalance in the distribution of the old age homes in Turkey. Due to this imbalance, the number of population per bed is between 67 as in istanbul and 1610 as in c;orum, while aged population rate is higher in c;orum than istanbul. On the other hand there is not any old age home in 37 districts, in some of them have the aged population is higher than average. Having high urbanisation rate, which reached 65% in 1997 and changing the family stile from a patriarchal to a nuclear family and the imbalance in the distribution of old age homes suggest that difficult days are ahead for ageing people.